2020
DOI: 10.1007/s00404-020-05568-5
|View full text |Cite
|
Sign up to set email alerts
|

The ovulation trigger–OPU time interval of different ovarian protocols in ART: a retrospective study

Abstract: Purpose To explore the trends of oocyte and pregnancy outcomes over the ovulation trigger-OPU (oocyte pickup) time interval in four mainly used COH protocols. Methods This retrospective study was conducted between January 2013 and July 2018. The IVF/ICSI cycles of the patients with normal ovarian reserve were included. The number of total patients was 4673, which consisted of long agonist protocol (n = 819), short agonist protocol (n = 1703), mild stimulation protocol (n = 1627), and GnRH antagonist protocol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…The competitive nature of pituitary suppression may be the reason for occasional escape. Although LH surge was observed in six patients, the exible advanced arrangement of oocyte retrieval allowed us to obtain oocytes and viable embryos in these patients [31,32].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The competitive nature of pituitary suppression may be the reason for occasional escape. Although LH surge was observed in six patients, the exible advanced arrangement of oocyte retrieval allowed us to obtain oocytes and viable embryos in these patients [31,32].…”
Section: Discussionmentioning
confidence: 98%
“…The GnRH-ant protocol is preferable for women with a good prognosis who would prefer shorter time to pregnancy. However, frequent monitoring is necessary, and the protocol has an unavoidable risk of late OHSS induced by pregnancy [31,32]. PPOS is a new, simpli ed protocol for ovarian stimulation that is appropriate for the freeze-only strategy.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the reported results of the clinical outcomes were different from ovulation trigger–OPU interval of different ovarian stimulation protocols on oocyte maturation and clinical outcomes [34–37,41] . The results of the present study showed that the clinical pregnancy rate (62.5% vs. 61.1%) and implantation rate (46.9% vs. 47.2%) did not differ between pre-IVF incubation for 5 hours with (+) and without (−) oocyte maturation medium (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Transvaginal ultrasound-guided oocyte retrieval was conducted 35–39 h after trigger [ 40 ]. All follicles > 10 mm in diameter were aspirated, with fertilization being achieved via conventional IVF or ICSI, depending on semen quality [ 41 ].…”
Section: Methodsmentioning
confidence: 99%